2021
DOI: 10.3390/medicina57030268
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of the Self-Expandable Metal Stent as a Bridge to Surgery Versus Emergency Surgery in Colorectal Cancer: Results from an Updated Systematic Review and Meta-Analysis of the Literature

Abstract: Background: The current use of endoscopic stenting as a bridge to surgery is not always accepted in standard clinical practice to treat neoplastic colonic obstructions. Objectives: The role of colonic self-expandable metal stent (SEMS) positioning as a bridge to resective surgery versus emergency surgery (ES) for malignant obstruction, using all new data and available variables, was studied and we focused on short- and long-term results. Materials and Methods: A systematic review with meta-analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…These concerns elicited surgeons to find a safer approach such as stent-first strategy. A recently published meta-analysis concluded a significantly higher rate of successful primary anastomosis in stenting than the emergency surgery group ( 39 ). Stent placement also favors mechanical bowel preparation finally resulting in end-to-end anastomosis without use of colostomy and stoma ( 40 ), thereby significantly improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns elicited surgeons to find a safer approach such as stent-first strategy. A recently published meta-analysis concluded a significantly higher rate of successful primary anastomosis in stenting than the emergency surgery group ( 39 ). Stent placement also favors mechanical bowel preparation finally resulting in end-to-end anastomosis without use of colostomy and stoma ( 40 ), thereby significantly improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stent placement has been recommended only in high-risk patients with an ASA score of 3 or higher and in patients older than 70 ( 32 ). Noteworthy, given that different studies brought different results and conclusions, stenting should be performed by endoscopist with adequate expertise ( 39 ). This could be a possible hypothesis as to why different studies have different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Cirocchi et al [ 54 ] conducted a systematic review and meta-analysis of RCTs and found that compared with ES, SEMS placement as BTS had a higher rate of successful primary anastomosis (RR: 1.26; 95%CI: 1.01-1.57), lower stoma rate (RR: 0.62; 95%CI: 0.45-0.85), and lower postoperative complication (RR: 0.61; 95%CI: 0.45-0.85). The mortality rate was comparable between the two modalities.…”
Section: Treatment Options For Lmcomentioning
confidence: 99%
“…Similarly, the CReST trial found a comparable 3-year recurrence rate and overall survival between SEMS as BTS and ES, with a low SEMS-related perforation rate of 3.3%[ 53 ]. The latest systematic review and meta-analysis of five RCTs by Cirocchi et al [ 54 ] revealed comparable recurrence rates and oncologic outcomes between SEMS placement as BTS and ES. We conducted a meta-analysis of these six RCTs that reported the recurrence rate.…”
Section: Oncologic Outcomes After Colonic Stenting In Curable Diseasementioning
confidence: 99%
“…The purpose of this review was to collect the latest (since 2020) research on SEMS for BTS use. In one of the more updated systematic reviews and meta-analyses[ 7 ], only two studies published after 2020 were included (Arezzo et al [ 8 ] multicentric study and Allievi et al [ 9 ] single center study). Both the international guidelines and the short-term/long-term outcomes focusing on the new data published after 2020 have been analyzed (the “update” part of each chapter).…”
Section: Introductionmentioning
confidence: 99%